Церкви Вороніжа - Кириєвський, В.Д. (Сіверщина в історії України, 2022)
У статті викладена історія церков містечка Вороніжа, колишнього адміністративного центру Воронізької сотні (1654–1781) Ніжинського полку. У статті наведені нові, раніше невідомі архівні документи, що були виявленні останнім часом. Також враховані новітні краєзнавчі публікації стосовно воронізьких церков, навіть задіяні німецькі аерофотографії 1942 р. Стаття стане в нагоді для складання оновлених туристських путівників до Вороніжа. The article presents the history of the churches of the town of Voronizh, the former administrative center of the Voronizh Hundred (1654–1781) of the Nizhyn Regiment. «Under the Hetmanate of Voronizh, one exhibited a hundred Cossacks and there were hundreds of administrations in it. Then the place was rich, commercial and crowded. That’s why there were up to 7 parish churches here. There was also a protopopia or spiritual rule». Such a laudable historical assessment of the Cossack Voronizh was given by the author of the «Historical and Statistical Description of the Chernihiv Diocese» of 1873, published by Archbishop Filaret of Chernihiv and Nizhyn (Humilevskyi) (1805–1866). Voronizh residents agree with the archbishop and believe that the oldest in the town was the Church of St. Nicholas. The image of the church with a bell tower in the village of Pirohivka of the Voronizh Hundred, depicted on a three-century plan drawn up on the day of the battle between the Swedes and Muscovites for crossing the Desna on October 26, 1708, gives an idea of its appearance, as well as the appearance of the first Cossack churches. This is a common one-headed church for the XVII century. There were such churches in every village of the Voronizh Hundred. They were probably built by a team of craftsmen. The St. Nicholas Church in Voronizh was built in the same way. It was mentioned by P. Kulish in his historical novel «Mikhail Chernyshenko or Little Russia 80 Years Ago» (1843). Proof of the existence of the Church of St. Nicholas is the name of the central corner of Voronizh – Mykilshchyna. Voronizh residents still say that the Church of St. Nicholas stood next to St. Michael’s Church, which is now replaced by the stone St. Michael’s Church, on the ground floor of which is the warm St. Nicholas Church. A century and a half ago in the town of Voronezh, Hlukhiv district, Chernihiv province, there were six churches: Mykhailivska, Uspenka, Troitska, Trohsvyatytelska, Preobrazhenska and Pokrovska. The article presents new previously unknown archival documents that have been discovered recently. The latest local lore publications on Voronizh churches are also taken into account, even German aerial photographs from 1942 are used. The article will be useful for compiling updated tourist guides to Voronizh.